Reading Ong reading McLuhan. Issue 9 (2nd September 2021) - Guillory, John
ABSTRACT: This essay offers an account of the ongoing exchange between Marshall McLuhan and Walter J. Ong, S.J. in the context of their shared interest in the print revolution of the early modern period, as well as their common embrace of Catholic theology. Ong did his Master's thesis under McLuhan's direction, and at his teacher's suggestion, went on to write a dissertation at Harvard on the figure of the Protestant philosopher, Petrus Ramus, published as Ramus, Method, and the Decay of Dialogue in 1958. McLuhan's work on media and the print revolution in the nineteen-fifties culminated in The Gutenberg Galaxy, his breakthrough study of 1962, which I argue is in some respects a response to Ong's study of Ramus. After the convergence of their interest in the nineteen-fifties, however, Ong rejected the concept of 'medium, ' focusing instead on the problem of 'orality and literacy.' This divergence, I further argue, was deeply rooted in the different ways that Ong and McLuhan assimilated Catholic theology. For Ong, McLuhan's commitment to the transformative possibilities of media implied a residually Protestant orientation of his thought, a reformism that Ong believed was incompatible with orthodox Catholic theology.